REGULACJA PRAWNA INTERPELACJI POSELSKICH W SEJMIE ŚLĄSKIM W LATACH 1922-1939 - Ciągwa, Józef (Zeszyty Prawnicze, 2016)
LEGAL REGULATION OF INTERPELLATIONS IN THE SILESIAN PARLIAMENT IN THE YEARS 1922-1939 Summary Article 14 of The Constitutional Act of 15 of July 1920 on Silesian autonomy granted the Silesian Parliament an important instrument of control of the administration of the autonomous voivodship in the form of the right to interpellate the Voivode and Voivodship Council. A specific procedure of the execution of this right was to be determined by the Silesian Act on the Internal Government of the Silesian Voivodship. However, the Silesian Parliament was not able to pass such legislation and the manner of interpellation was determined – as adopted in the form of parliamentary resolutions – by the Rules of the Session of the Silesian Parliament (of 13 October 1922; 31 January 1923; 17 June 1930; 11 March 1936). Each particular set of these rules of the session referred to the rules of the session of the Parliament of the Republic of Poland. The reception of all-Polish rules of interpellation concerned obviously only the basic rules, as the specific decisions (e.g. concerning the interpelled organs; the scope of support given to interpellation; the terms) were naturally different. The uncritical use of all-Polish patterns of interpellation led to the Silesian Parliament being granted upon The Rules of the Session of 17 June 1930 the right to interpellate the Council of Ministers; and to the removal of The Voivodship Council from interpellated organs – upon The Rules of the Session of 11 March 1936. These solutions were contrary to Article 14 of the Constitutional Act of 15 July 1920 on the Silesian Autonomy. The Silesian Rules of the Session, adopted 11 March 1936, formed according to The Rules of the Session of the Parliament of the Polish Republic (of 5 October 1935) contained some solutions which were contrary to the classic solutions of the interpellation procedure: facultative debate over the interpellation and reply; disposing the Parliament of the right to pass a resolution on whether to accept or not the Voivode’s reply. These solutions did not favour the effectiveness of the interpellation process.